Conceptualisation of financial exploitation of older people: a review - Che Amani @ Mohd Kamal, Nurfadhilah; Kahar, Rojanah; Ibrahim, Rahimah; Hasbullah @ Abdullah, Muslihah (Universiti Putra Malaysia Press, 2021)
The concept of financial exploitation has gained much interest in the field of elder abuse. The purpose of this study is to review the conceptualisation of elder financial exploitation as a first step towards exploring how financial abuse is interpreted differently by different groups. The search strategy includes the use of the SCOPUS database, including PubMed, MEDLINE, and open access for articles published between 1997 and January 2019. This study includes prevalence studies regarding the analysis of perceptions and conceptualisation of financial exploitation. This study excluded studies published in languages other than English with no relevance regarding the focus of the study. Twentysix studies met the inclusion criteria with four categories (older people, professional, public, and family members) and a range of settings across studies. Three overarching themes emerged in this review. The sub-themes include values, expectations, cultural considerations, characteristics of older people, relationship dynamics, situational factors, knowledge, and attitudes. Current evidence supports the on-going discussion on the lack of uniformity in definitions and conceptualisations of the financial exploitation of older people. The lack of consideration from the views of older people and community members may add to the complexity of defining financial exploitation, which can result in problems in detection, disclosure, and underreporting incidences.